Genome-wide association study using specific-locus amplified fragment sequencing identifies new genes influencing nitrogen use efficiency in rice landraces - Liao, Zuyu; Xia, Xiuzhong; Zhang, Zongqiong; Nong, Baoxuan; Guo, Hui; Feng, Rui; Chen, Can; Xiong, Faqian; Qiu, Yongfu; Li, Danting; Yang, Xinghai (Frontiers in Plant Science, 2023)
Nitrogen is essential for crop production. It is a critical macronutrient for plant growth and development. However, excessive application of nitrogen fertilizer is not only a waste of resources, but also pollutes the environment. An effective approach to solve this problem is to breed rice varieties with high nitrogen use efficiency (NUE). In this study, we performed genome-wide association study (GWAS) on 419 rice landraces using 208,993 SNPs. With the mixed linear model (MLM) in Tassel software, we identified 834 SNPs associated with root surface area (RSA), root length (RL), root branch number (RBN), root number (RN),plant dry weight (PDW), plant height (PH), root volume (RL),plant fresh weight (PFW), root fractal dimension (RFD), number of root nodes (NRN), and average root diameter (ARD), with a significant level of p < 2.39×10–7. In addition, we found 49 SNPs that were correlated with RL, RBN, RN, PDW, PH, PFW, RFD and NRN using genome-wide efficient mixed model association (GEMMA), with a significant level of p < 1×10–6. Within the linkage intervals of significantly associated SNP, there were 8 known related-genes to NUE in rice, which were OsAMT2;3, OsGS1, OsNR2, OsNPF7.4, OsPTR9, OsNRT1.1B, OsNRT2.3, and OsNRT2.2. According to the linkage disequilibrium (LD) decay value of this population, there were 75 candidate genes in the 150-kb regions upstream and downstream of the most significantly associated SNP Chr5_29804690, Chr5_29956584 and Chr10_17540654, including 22 transposon genes, 25 expressed genes, and 28 putative function genes. The expression levels of these candidate genes were identified by RT-qPCR, and the results showed that the expression levels of LOC_Os05g51700 and LOC_Os05g51710 in C347 were significantly lower than in C117; and the expression levels of LOC_Os05g51740, LOC_Os05g51780, LOC_Os05g51960, LOC_Os05g51970 and LOC_Os10g33210 were significantly higher in C347 than C117. Among them, LOC_Os10g33210 encodes a peptide transporter, and LOC_Os05g51690 encodes a CCT domain protein and responds to NUE in rice. This study identified new loci related to NUE in rice, which can provide new genetic resources for the molecular breeding of rice landraces with high NUE.